Kemiskinan dan Alat Ukur Kemiskinan dalam Islam - Nurul Fadila (Journal on Education, 2023)
In everyday life, poverty is something that is real in society. Poor people are not only in developing countries, but also in developed countries. Thus the problem of poverty exists in this world, both in developed countries and developing countries like Indonesia. The problem of poverty has always received major attention in Indonesia. This happened because of the government's awareness that failure to overcome the problem of poverty would lead to the emergence of various social, economic and political problems in society. The efforts made by the government are carrying out economic development and reducing poverty. Indonesia's success in carrying out economic development and reducing poverty has received praise from the world community. Unfortunately, not long after, Indonesia experienced an economic crisis in mid-1997, so that Indonesia was hit by a crisis storm that caused Indonesia to really fall. This crisis condition began with the exchange rate of the rupiah against the United States dollar and then turned into a total crisis in which this total crisis covered all aspects of people's lives. By using a deductive research process with quantitative research methods or empirical research. The results of this study can find out poverty data and measuring instruments used according to Islamic views.